La jerga del béisbol como herramienta discursiva en la política venezolana: el caso de Hugo Chávez (PHRASIS | Rivista di studi fraseologici e paremiologici, 2021)
It is usual in Venezuela that politicians exploit the use of phraseological units (PU) related to baseball (a major sport), to establish affective relationships of different types between their potential voters and their potential adversaries. Hugo Chávez (1999-2013) stands out for having used these expressions as discursive tools during his career as President of Venezuela. Starting from a corpus of electoral campaign speeches containing PU used by him and mostly formed with the lexicon of baseball jargon, we present a study with two objectives: i) to analyze the nature of these units (in context and co-text), based on the concepts of variationist sociolinguistics; and ii) to explain, considering the sense of these units, the pragmatic –and political– aims that the enunciator seems to pursue with them. Our analysis shows, in summary, the way in which Hugo Chávez creates close emotional bondings with his followers and a controversial relationship of rejection and distancing from his political adversaries through the aforementioned PU.
Keywords: political discourse, baseball, Hugo Chávez, Venezuela